PENGARUH PERSEPSI KEMUDAHAN, KEMANFAATAN, KEAMANAN DAN MINAT TERHADAP KEPUTUSAN PENGGUNAAN QRIS PADA GENERASI Z DI KOTA DENPASAR - Yuuka Narita Putri, Ni Made; R. Aprilyani Dewi, Putu Pande; Jaya Kusuma, Putu Sri Arta; Laksmi P, Kadek Wulandari (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to determine the effect of convenience, usefulness, security and interest partially and simultaneously on the decision to use. The sample in this study was Generation Z aged 17-26 years, who used the Quick Response Code Indonesian Standard (QRIS) and were domiciled in Denpasar City as many as 114 people. The data analysis technique used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and t Test. From the results of the study, it was found that convenience had a positive and significant effect on the decision to use, usefulness had a positive and significant effect on the decision to use, security had a positive and significant effect on the decision to use, interest had a positive and significant effect on the decision to use and convenience, usefulness, security and interest had a significant effect on the decision to use. The magnitude of the influence of the independent variables on the decision to use is 65.3%.